2004
DOI: 10.1073/pnas.0306845101
|View full text |Cite
|
Sign up to set email alerts
|

Outer-surface protein C of the Lyme disease spirochete: A protein induced in ticks for infection of mammals

Abstract: Environmentally responsive synthesis of surface proteins represents a hallmark of the infectious cycle of the Lyme disease agent, Borrelia burgdorferi. Here we created and analyzed a B. burgdorferi mutant lacking outer-surface protein C (OspC), an abundant Osp that spirochetes normally synthesize in the tick vector during the blood meal and down-regulate after transmission to the mammal. We demonstrate that B. burgdorferi strictly requires OspC to infect mice but not to localize or migrate appropriately in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
430
2
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 377 publications
(460 citation statements)
references
References 43 publications
(30 reference statements)
22
430
2
4
Order By: Relevance
“…Similarly, Mn, possibly via the Mn-dependent Fur homolog BosR (23,33,37,38) Our study has demonstrated that the Lyme disease spirochete requires BmtA's Mn-associated transport function(s) to maintain its infectious cycle in nature. To date, only relatively few virulence factors, including OspC, DbpB/A, OspA/B, PncA, and BptA, have been identified in Bb, and the functions of most of these proteins remain obscure (4,5,(7)(8)(9)(10). In this regard, our identification of BmtA as a novel virulence factor in Bb provides further insights into molecular mechanisms that contribute to Bb's survival in nature and may lead to new strategies to interrupt the spirochete life cycle.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, Mn, possibly via the Mn-dependent Fur homolog BosR (23,33,37,38) Our study has demonstrated that the Lyme disease spirochete requires BmtA's Mn-associated transport function(s) to maintain its infectious cycle in nature. To date, only relatively few virulence factors, including OspC, DbpB/A, OspA/B, PncA, and BptA, have been identified in Bb, and the functions of most of these proteins remain obscure (4,5,(7)(8)(9)(10). In this regard, our identification of BmtA as a novel virulence factor in Bb provides further insights into molecular mechanisms that contribute to Bb's survival in nature and may lead to new strategies to interrupt the spirochete life cycle.…”
Section: Discussionmentioning
confidence: 95%
“…In recent years, extensive efforts have been directed toward elucidating the mechanisms by which Bb cycles, adapts, and sustains itself in these diverse niches. It is now well established that outer surface (lipo)protein C (OspC), OspA/B, decorin-binding protein B/A (DbpB/A), PncA, and BptA are required by Bb for efficient infection of ticks or mammalian hosts (4)(5)(6)(7)(8)(9)(10). It is also generally accepted that the recently discovered Rrp2-RpoN ( 54 )-RpoS ( S ) regulatory pathway plays prominently in Bb's virulence expression (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…While specific molecular functions of OspC are not yet clear, it is known that ospC is required for host infection and is among the most differentially expressed genes during host invasion (Brooks et al 2003;Grimm et al 2004;Liang et al 2004;Tilly et al 2006;Antonara et al 2010). Considering that ospC is a serotype determinant of B. burgdorferi s.l., negative FDS operating at ospC is highly plausible.…”
Section: Maintenance Of Genome Clusters By Frequency-dependent Selectionmentioning
confidence: 99%
“…Some are involved in early infection, such as OspC [112][113][114][115][116], which are presumably required for host colonization or resistance to innate immunity. Others are involved in resistance to acquired immunity, such as VlsE [13,109,117,118].…”
Section: B Burgdorferi Products Required For Mammalian Infectionmentioning
confidence: 99%
“…The OspC product has been shown to be required for an early stage of mammalian infection [113][114][115][116] and conflicting data have been presented regarding its importance in tick transmission [113,114,119,120]. OspC production begins in feeding ticks (or immediately after needle inoculation, Fig.…”
Section: B Burgdorferi Products Required For Mammalian Infectionmentioning
confidence: 99%